A modified tarsorrhaphy in patients with facial nerve palsy. Issue 9 (September 2019) - Feldman, Ilan; Ben Cnaan, Ran; Bar-Niv, Zehavi; Leibovitch, Igal
Abstract: Purpose: We report our experience with a modified tarsorrhaphy (MT) technique in patients with facial nerve palsy (FNP). Methods: This study involved a retrospective chart review of patients with FNP undergoing MT over a 10-year period in one Medical Center. Patient demographics, presence of lagophthalmos, occurrence of eyelid malpositions, recurrent retraction, and repeat procedures were noted from medical records. Results: Twenty patients (11 females, mean age 38 years) were included. Mean follow-up was 41 months (range 6–132). All patients had lagophthalmos prior to surgery compared with four on last follow-up. The number of patients with punctate epithelial erosions (PEEs) reduced from nine preoperatively to five postoperatively. While seven patients used lubricating drops prior to surgery, two stopped lubrication completely and five reduced the amount after surgery. No patients developed a new-onset lower eyelid malposition. No recurrence or postoperative complications were noted. Conclusion: This MT technique avoids grey line split and excision of orbicularis muscle or skin. It improves lower eyelid retraction and reduces lagophthalmos in FNP.